3D cost optimization of 3 story RC constructional building using Jaya algorithm. (June 2022) - Aslay, Semi Emrah; Dede, Tayfun
Abstract: Studies on the optimization of reinforced concrete structures are mostly carried out in 2D. This situation causes insufficient accurate results to be obtained in the optimization analyses of reinforced concrete (RC) structures. For this reason, studies on the optimization of RC 3D structures have been started in recent years. However, in these studies, real-world structures have not yet been fully used in terms of having RC shear walls Mergos (2021) [1] because real world RC structures mostly consist of not only RC frames, but also reinforced concrete shear walls and frames. In this study, a real-world 3D RC structure is used. The structure used in the numerical application consists of RC shear walls and frames. Cost and design optimization is done automatically on a 3D structure by using a new software ACDOS (Automated Cost and Design Optimization of Structures) developed by the authors using the ETABS-OAPI files into MATLAB programming. As a numerical example, 3D RC structure is optimized with the Jaya algorithm and successful results are obtained.